Debated issues in sovereign predestination: early lutheran predestination, Calvinian reprobation, and variations in Genevan lapsarianism - Beeke, Joel R. (Reformed historical theology, 2017)
"Joel R. Beeke examines three flashpoints of controversy in Reformation and Post-Reformation theology: first, the development of the Lutheran doctrine of predestination from Martin Luther and Philip Melancthon to the Formula of Concord; second, the doctrine of repbrobation as traced through the writings of John Calvin; and third, the doctrine of predestination in Geneva from Theodore Beza in the sixteenth century to Jean-Alphonse Turretin and Jacob Vernet in the eighteenth century. This books offers a balanced, historical analysis of a difficult subject." -- From back of book